Bimbingan Kelompok sebagai Intervensi Humanistik untuk Mengurangi Kebiasaan Merokok pada Santri di Pondok Pesantren Miftahul Huda - M. Mazidul Akmal Shiddiq; Galih Fajar Fadillah; Angga Eka Yuda Wibawa; Ulvina Rachmawati; Triyono (LaKaspia, 2025)
Purpose: This study aims to analyze the effect of group guidance services on smoking habits among santri at Miftahul Huda Islamic Boarding School, Bojonegoro. Smoking behavior among adolescents, including santri, constitutes a serious problem due to its detrimental impact on physical health, psychological well-being, and academic performance. Group guidance services are considered an effective intervention to prevent and reduce smoking behavior through supportive and constructive group dynamics. Method: This research employed a quantitative experimental approach using a one-group pretest–posttest design. The sample was selected through purposive sampling, focusing on santri who met the criteria as active smokers. Data were collected using a smoking habit scale that had been tested for validity and reliability. Data analysis was conducted using the Paired Sample t-Test. Results: The findings revealed a statistically significant difference in smoking habits before and after the intervention, as indicated by a decrease in the mean score of smoking behavior following the implementation of group guidance services. Conclusion: These results indicate that group guidance services are effective in reducing smoking habits among santri at Miftahul Huda Islamic Boarding School, Bojonegoro. This study highlights the potential of group-based counseling interventions as a preventive and corrective strategy for addressing health-risk behaviors within the pesantren educational context.